INTERNATIONAL COMPETITIVENESS OF THE ENTERPRISE - Yanton-Drozdovska , E. (The actual problems of regional economy development, 2020)
Abstract. Competition characterizes the relationships between entities and occurs in the field of economic, social, cultural and artistic relations, and of course sports. Nowadays, competition is most often understood as competition and rivalry between entities striving to achieve the same goal and the same benefits on a global scale. International (global) competition is commonly understood as competition between companies or countries on a global scale and is the most visible dimension of globalization. The emergence of global competition is mainly associated with changes that have taken place in the external environment of enterprises. Success in global competition can only be ensured by an action strategy that is focused on innovation, creates a system of rapid response to emerging opportunities and threats, enables active impact on factors shaping production and demand in the sector, on competitors, and related and supporting sectors. An effective strategy should also take into account the directions of internationalization or globalization of the company's operations, possible strategic alliances and the right location supporting competitive advantage. The globalization of knowledge and technology includes the intensification of international integration in the sphere of research and development and in the sphere of technology implementation, expanding international cooperation between companies from different countries sharing know how, as well as cooperation between governments and academic institutions, and an increase in the use of innovation on a global scale. In the conditions of global competition, people and their knowledge have become a strategic resource. The increase in intellectual capital efficiency depends on the ability and ability to associate it with abundant, and therefore cheap, factors located on the global market. Globalization, leading to the free possibility of production factors across borders, creates such possibilities. External and internal factors (determinants) of the international competitiveness of the enterprise are considered. The most important determinants of the so-called the company's closer environment is found out. These determinants remain in close dependence and interactive relationship with elements of the macroeconomic environment, primarily with economic, social, legal and political factors. They are independent of the enterprise, as they largely depend on the state policy, the degree of market regulation and, in general, the economic situation in a given country and in the global economy. In turn, internal factors determining the competitiveness of an enterprise in an ideal perspective depend on the enterprise itself, its resources and activities. However, one should remember about the interactivity highlighted above for all the determinants of competitiveness. The company has an impact on all of these factors, but their positive impact on improving competitiveness, competitive position and finally achieving the desired competitive advantage is also conditioned by external determinants of competitiveness.